2000
DOI: 10.1128/jcm.38.3.1023-1031.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Shiga Toxin-Producing Escherichia coli Isolated from Cattle, Food, and Children during a One-Year Prospective Study in France

Abstract: During a 1-year survey of Shiga toxin-producing Escherichia coli (STEC) prevalence in central France, 2,143 samples were investigated by PCR for Shiga toxin-encoding genes. A total of 330 (70%) of 471 fecal samples collected from healthy cattle at the Clermont-Ferrand slaughterhouse, 47 (11%) of 411 beef samples, 60 (10%) of 603 cheese samples, and 19 (3%) of 658 stool specimens from hospitalized children with and without diarrhea were positive for thestx gene(s). A STEC strain was isolated from 34% (162 of 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
111
5
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(143 citation statements)
references
References 33 publications
19
111
5
8
Order By: Relevance
“…The data obtained showed that 73.8% of the STEC strains were sensitive to all the antimicrobials tested, consistent with results from studies conducted in different countries (Pradel et al, 2000;Eklund et al, 2001;Bettelheim et al, 2003). Curiously, the highest frequency (47.6%) of resistance was found among the human STEC strains, in contrast to the results described by Schroeder et al (2002), who detected a higher level of resistance among cattle non-O157 STEC strains than among human strains, but in agreement with the results observed by Pradel et al (2000) and Mora et al (2005). Although resistance was observed in some particular serotypes, multidrug resistance (three to six antimicrobials) was only identified among O111:H8(NM) STEC strains from human and bovine origins, and in one human ONT:H2 strain.…”
Section: Resultssupporting
confidence: 88%
“…The data obtained showed that 73.8% of the STEC strains were sensitive to all the antimicrobials tested, consistent with results from studies conducted in different countries (Pradel et al, 2000;Eklund et al, 2001;Bettelheim et al, 2003). Curiously, the highest frequency (47.6%) of resistance was found among the human STEC strains, in contrast to the results described by Schroeder et al (2002), who detected a higher level of resistance among cattle non-O157 STEC strains than among human strains, but in agreement with the results observed by Pradel et al (2000) and Mora et al (2005). Although resistance was observed in some particular serotypes, multidrug resistance (three to six antimicrobials) was only identified among O111:H8(NM) STEC strains from human and bovine origins, and in one human ONT:H2 strain.…”
Section: Resultssupporting
confidence: 88%
“…The stx-PCR-positive faecal samples were detected from 178 (37.2%) of 479 beef cattle, 38 (39.2%) of 97 cull cows and 11 (37.9%) of 29 F1 cattle ( Table 2), but these rates were not statistically different (P > 0.05) by t-test. In recent screening work on slaughtered cattle with stx-PCR, rates have varied between 18% and 70% in France [36,37], Australia [26] and Canada [17]. In Japan, rates have also varied between 39% and 79% at breeding or dairy farms [6,38] and were recovered at 41% at a slaughterhouse [38] in Japan.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, O157:H7 has rapidly spread into dairy and beef farms worldwide since this serotype was first described in 1983 [12], although the route of transmission is unclear. Recent reports described O157:H7/-infection rates in slaughtered cattle and/or cows at 1.3-28% in the United States [42,43], 16.1-16.6% in Italy [44], 10.6% in The Netherlands [45], 4.0-4.7% in England [8,13], 0.2% in France [36] and 1.6-8.1% in Japan [5]. According to these reports, although these differences are likely due to differences in culture methods, remarkable differences were found in the rates of recovery of O157:H7 isolates for slaughtered animals in various geographic areas.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in central France, from August 1996 to May 1997, six STEC strains including two O91 were isolated from stool specimens of adults suffering from HUS (Bonnet et al 1998). A STEC prevalence study in the same geographical area showed that O91 was the fourth major serogroup of STEC obtained from cattle, beef, cheese and children with 12 isolates among the 203 typeable strains obtained (Pradel et al 2000). Moreover, another epidemiological survey for STEC in French dairy products gave two O91 isolates among 34 STEC strains (Fach et al 2001).…”
Section: Discussionmentioning
confidence: 99%